2012
DOI: 10.1186/1471-230x-12-111
|View full text |Cite
|
Sign up to set email alerts
|

The i148m Pnpla3 polymorphism influences serum adiponectin in patients with fatty liver and healthy controls

Abstract: BackgroundReduced adiponectin is implicated in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH), and the I148M Patatin-like phospholipase domain-containing 3 (PNPLA3) polymorphism predisposes to NAFLD and liver damage progression in NASH and chronic hepatitis C (CHC) by still undefined mechanisms, possibly involving regulation of adipose tissue function. Aim of this study was to evaluate whether the I148M PNPLA3 polymorphism influences serum adiponectin in liver diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 40 publications
5
48
3
Order By: Relevance
“…Thus, PNPLA3 rs738409 has been functionally linked to increased levels of circulating pro-inflammatory mediator intracellular adhesion molecule 1 (ICAM-1) [27], which is also overexpressed in human HCC stem cells and circulating HCC tumor cells [28]. Furthermore, in patients with NAFLD PNPLA3rs738409 G allele was found to be associated with decreased levels of adiponectin which has important anti-inflammatory, anti-fibrotic and anti-carcinogenic properties [29]. Recent data in cell culture and mice xenografts also suggest an effect of PNPLA3 rs738409 on the activation of the interleukin (IL)-6-Janus kinase (JAK2)/Signal Transducers and Activators of Transcription (STAT3) pathway via fatty acid-mediated inflammation [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PNPLA3 rs738409 has been functionally linked to increased levels of circulating pro-inflammatory mediator intracellular adhesion molecule 1 (ICAM-1) [27], which is also overexpressed in human HCC stem cells and circulating HCC tumor cells [28]. Furthermore, in patients with NAFLD PNPLA3rs738409 G allele was found to be associated with decreased levels of adiponectin which has important anti-inflammatory, anti-fibrotic and anti-carcinogenic properties [29]. Recent data in cell culture and mice xenografts also suggest an effect of PNPLA3 rs738409 on the activation of the interleukin (IL)-6-Janus kinase (JAK2)/Signal Transducers and Activators of Transcription (STAT3) pathway via fatty acid-mediated inflammation [30].…”
Section: Discussionmentioning
confidence: 99%
“…For preparation of genotyping, DNA samples were evaluated by gel electrophoresis and adjusted to [20][21][22][23][24][25][26][27][28][29][30] ng/µl DNA content using the Picogreen fluorescent dye (Molecular Probes -Invitrogen, Carlsbad, Ca, USA) on a robotic platform using TECAN liquid handling equipment. One microliter of genomic DNA was amplified with the GenomiPhi (Amersham, Uppsala, Sweden) whole genome amplification kit and fragmented at 99°C for three minutes.…”
Section: Dna Preparation and Genotypingmentioning
confidence: 99%
“…Valenti et al have showed that rs738409 single nucleotide polymorphism of PNPLA3, encoding for a protein variant (I148M), influences hepatic triglycerides accumulation, the susceptibility to fibrosis, the response to antiviral treatment and may represent a genetic determinant of adiponectin levels in CHC. 17,18 The relevance of genetics in the development of liver steatosis and adiponectin changes in CHC is confirmed in this study by the description of the role of IFNL3 genotype CC. The significant impact of relatively frequent genetic variants, such as the PNPLA3 I148M or the IFNLA3 genotype CC, suggests some important considerations: 1) genetic variants affecting tissue-specific proteins, like the adipokines, may have both localized or systemic effects, involving apparently separate systems, such as adipose tissue, liver, and immune system, and providing a mechanistic link to understand the pathogenesis of several multifactorial disorders; 2) in the future, diagnosis and management of liver disorders should take into account the genetic background of each patient, since this could have serious consequences on the evolution and the prognosis of the disease.…”
supporting
confidence: 55%
“…The I148M PNPLA3 genotype may represent a genetic determinant of serum adiponectin levels. Therefore, in carriers of the 1148M PNPLA3 variant, modulation of serum adiponectin might be involved in mediating the susceptibility to steatosis [44] .…”
Section: Role Of Leptin Adiponectin Resistin and Retinol Binding Pmentioning
confidence: 99%